Svetovalno delo v vrtcu - Mlinarič, Mateja (Socialno delo, 2017)
Based on interviews, the author examines the importance of social work in counselling in early childhood education and at the same time looks at connections among social work, consulting work, and the perspectives of employees in the kindergarten on advisory work. As a social worker in the kindergarten context strives to develop creative cooperation of all participants, the quality of the kindergarten increases. Due to her/his "bilingual" skills (ability to use an expert terminology and a simple language of users), a social worker is a great asset for the kindergarten, but may be faced with a particular danger of becoming an overburdened and overstressed jack-of-all-trades for problems of all participants. Namely, she/he has to deal with individual and group work, children with behaviour challenges, administration and relations with employees.
Keywords: social work; socialno delo; svetovalno delo; predšolska vzgoja; strokovne kompetence; delovni odnos; soustvarjanje; education; izobraževanje